The Contribution of Various Training Program Models to Improve the Athletic Performance - Selenica, Rigerta (European Journal of Multidisciplinary Studies, 2022)
In many sporting disciplines, a person’s ability to jump is an excellent measure of their physical characteristics. Trainers are constantly searching for the greatest training techniques or methods that significantly expand the vertical jump’s possibilities. The quest for techniques that can help boost one’s vertical jump capacity is linked to the hope of succeeding, and as a result, success in many sports is linked to having a high vertical jump. The study’s objective was to assess the indicators of vertical jump by classifying them according to the utilization of exercises using various strength-building techniques. This material was chosen by several research fields that rely on books and the internet. The randomly subjects’s from the Tirana Sports University are the center of our investigation. The Leonardo Mechanograph® GRFP standard variant of STD was used to gather data for contact time and vertical jump height. In comparison to the control group for 12 weeks, the findings of the jump indicators have changed as a result of the training programs implemented. Changes in the indicators of vertical jump height and ground contact time reaction values were discovered through our study case. The three training models all had an impact on jumping ability, but the maximum strength and plyometric exercise approach had the biggest effect in our study based on the significance of the collected data.